2011
DOI: 10.1681/asn.2010090907
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Mutations in Gitelman Syndrome

Abstract: Gitelman's syndrome (GS) is a rare, autosomal recessive, salt-losing tubulopathy caused by mutations in the SLC12A3 gene, which encodes the thiazide-sensitive NaCl cotransporter (NCC). Because 18 to 40% of suspected GS patients carry only one SLC12A3 mutant allele, large genomic rearrangements may account for unidentified mutations. Here, we directly sequenced genomic DNA from a large cohort of 448 unrelated patients suspected of having GS. We found 172 distinct mutations, of which 100 were unreported previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
194
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 200 publications
(208 citation statements)
references
References 29 publications
8
194
2
2
Order By: Relevance
“…5,21 By contrast, the clinical manifestations of type III BS and GS may vary and resemble each other. 7,[11][12][13] Furthermore, p-BS/GS is difficult to distinguish from type III BS or GS because its clinical features match those of the latter two diseases. Correctly distinguishing these three diseases based on their clinical characteristics is thus important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,21 By contrast, the clinical manifestations of type III BS and GS may vary and resemble each other. 7,[11][12][13] Furthermore, p-BS/GS is difficult to distinguish from type III BS or GS because its clinical features match those of the latter two diseases. Correctly distinguishing these three diseases based on their clinical characteristics is thus important.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of type III BS were previously reported to show features similar to those of GS, including hypomagnesemia and hypocalciuria. 7,[11][12][13] In addition, one report published in 2003 showed that, in a large consanguineous family, both the BS and GS phenotypes were present with the same CLCNKB mutation. 13 In the same year a review article pointed out the phenotypic overlaps between type III BS and GS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Centre Hospitalier Pierre Oudot de Bourgoin-Jallieu, Service 23 de Pédiatrie, Bourgoin-Jallieu, France. 32 Methods: Genetic analyses were performed by direct sequencing and multiplex ligation-7 dependent probe amplification; medical charts were analyzed retrospectively for 115 patients 8 with CLCNKB mutations. Functional analyses were performed in Xenopus laevis oocytes for 9 eight missense and two nonsense mutations.…”
mentioning
confidence: 99%